Reversible Tuning of Ferromagnetism and Resistive Switching in ZnO/Cu Thin Films - Younas, Muhammad (ACS Omega, 2017)
[Image: see text] Systematic magnetic, electronic, and electrical studies on the Cu(0.04)Zn(0.96)O/Ga(0.01)Zn(0.99)O cell structure grown on (001) sapphire by the pulsed laser deposition technique show that the Cu multivalent (Cu(M+)) ions modulate magnetic and resistive states of the cells. The magnetic moment is found to be reduced by ∼30% during the high resistance state (HRS) to low resistance state (LRS) switching. X-ray photoelectron spectroscopy results reveals an increase of the Cu(+)/Cu(2+) oxidation state ratio (which has been determined by the relative positions of the Fermi level and the Cu acceptor level) during the HRS to LRS transition. This decreases the effective spin-polarized Cu(2+)–V(ö)–Cu(+) channels and thus the magnetic moment. A conduction mechanism involving the formation of conductive filaments from the coupling of the Cu(M+) ions and V(ö) has been suggested.